2011
DOI: 10.1208/s12249-011-9738-3
|View full text |Cite
|
Sign up to set email alerts
|

Solubility-Modulated Asymmetric Membrane Tablets of Triprolidine Hydrochloride: Statistical Optimization and Evaluation

Abstract: Abstract. The aim of the present study was to develop asymmetric membrane (AM) tablets for controlled delivery of highly water-soluble antihistaminic drug triprolidine hydrochloride. The solubility of triprolidine hydrochloride was modulated through the incorporation of coated sodium chloride crystals encapsulated with asymmetric membrane coating polymer, cellulose acetate butyrate. Formulation of AM tablets was based on a 2 3 factorial design to study the effect of formulation variables, namely, polymer conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…The results concluded that, when osmogen and pore former were at high levels in FAMC6 and FAMC8, higher release (average release,~92%) was observed than FAMC1 and FAMC2 (average release,~85%), having lower levels of both variables. The effect is attributable to the combined result of increased perforation of the capsular wall and osmotic gradient that has been documented in our previous studies (8)(9)(10)(11). Fig.…”
Section: In Vitro Drug Releasesupporting
confidence: 56%
See 4 more Smart Citations
“…The results concluded that, when osmogen and pore former were at high levels in FAMC6 and FAMC8, higher release (average release,~92%) was observed than FAMC1 and FAMC2 (average release,~85%), having lower levels of both variables. The effect is attributable to the combined result of increased perforation of the capsular wall and osmotic gradient that has been documented in our previous studies (8)(9)(10)(11). Fig.…”
Section: In Vitro Drug Releasesupporting
confidence: 56%
“…The incorporation of higher amount of coated NaCl (FAMC4, FAMC6, FAMC7, and FAMC8) resulted in the development of significant osmotic pressure inside the capsular core, and at the same time, the presence of the common ion Cl − reduced the solubility of RHCl that could have resulted in decreased release of RHCl. However, the generation and maintenance of the osmotic gradient for a longer duration due to the coated NaCl crystals counteracted the suppression in release (11), and hence, higher drug release was observed at 12 h from these formulations (~93%) when compared to the formulation made with lower levels of coated NaCl (FAMC1, FAMC2, FAMC3, and FAMC5) that displayed release to the order of~87% in 12 h.…”
Section: In Vitro Drug Releasementioning
confidence: 97%
See 3 more Smart Citations